A fundamental study on the relationship between barley cultivar and hordeins in single cultivar beers. Issue 2 (21st April 2016) - Taylor, Joshua P.; Arendt, Elke K.
Abstract : The hordein proteins found in beer are not suitable for gluten‐sensitive consumers. Hordeins are storage proteins found in barley and have limited solubility in water. It is not currently known if the nitrogen concentration of barley directly impacts on the hordeins present in beer. In this study a controlled malting on eight barley cultivars was performed and a single cultivar model beer was produced from each. The single cultivar model beers were then examined for differences in content of hordeins. The quality of barley and malt was assessed and the parameters measured were compared with the beer hordeins using a Pearson correlation matrix. The results showed significant differences in the content of beer hordeins, depending on the barley malt used. Correlations between results showed a positive relationship to malt nitrogen and a negative relationship to friability. The results suggest it may be possible to optimize the choice of the barley cultivar and the malting conditions in order to produce a beer low in hordeins. Copyright © 2016 The Institute of Brewing & Distilling